Graphitic carbon nitride nanospheres as an adsorbent for effective waste water treatment: Methylene Blue removal from aqueous medium - Pingal Sarmah; Khemnath Patir; Sonit Gogoi (Journal of Water and Environmental Nanotechnology)
Here we report a simple and eco-friendly solvothermal synthesis of graphitic carbon nitride nanospheres (g-CNNS) at 180 oC. The synthesized g-CNNS is characterized by various analytical techniques such as FESEM, PXRD, BET isotherm, Zeta potential, EDX and FT-IR spectroscopy. The adsorption property of g-CNNS is studied using four different dyes in aqueous medium and found that g-CNNS is an efficient material for cationic dye adsorption. A Comprehensive investigation of the kinetics, isotherms and thermodynamics of methylene blue (MB) adsorption, is carried out. The adsorption of MB on g-CNNS is well described by Langmuir isotherm model, and the experimental data fits well with pseudo-second order kinetics. The high rate of adsorption (94.92% MB removal in 120 minute at neutral pH) is attributed to electrostatic interaction between negative charged g-CNNS and cationic organic dye molecule. Additionally, g-CNNS demonstrated good reusability, retaining its efficiency for at least three cycles. Over all our findings suggests that g-CNNS has potential as an efficient adsorbent for wastewater treatment.